Giant vesical calculus - Vergadia, Ankita; Bansal, Neeraj; Gupta, Nitin (International Journal of Research in Medical Sciences, 2019)
Author presented a case report of a 42-year-old male patient who presented with dysuria, heaviness in lower abdomen since last 3 years associated with pain over bilateral lumber region since 2 years. He had history of recurrent urinary tract infection for last 6 months with blood in urine occasionally. Routine urine examination detected red and white blood cells with culture growth of E. coli. Ultrasound of abdomen confirmed the presence of vesical calculus of 10x7x5 cm.